STUDENTS 'ABILITY TO SOLVE RANDOM CHANGE PROBLEMS AND DISTRIBUTION OF OPPORTUNITIES IN THE ERA OF COVID-19 - Emy Artuti; Uminastuti; Pantur Pandiangan; Muhammad Hamdani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2021)
The ability to solve problems is one of the abilities that mathematics students must have in order to become a capable problem solver. This study aims to describe the ability of the fifth semester students of the Mathematics Education Study Program, Mathematics and Natural Sciences Education Department, Faculty of Mathematics and Natural Sciences, University of Palangka Raya in solving problems on the random variable material and the distribution of opportunities. The research instrument consisted of 2 questions consisting of one routine question and one non-routine question. The subjects in this study were students of the Mathematics Education Department of Mathematics and Natural Sciences Education, Faculty of Teacher Training and Education, University of Palangka Raya, who programmed the Mathematics Statistics I course in the fifth semester of class B academic year 2020/2021 as many as 26 students. The results showed that only 8 people (30.8%) were able to complete routine questions perfectly and 18 people (69.2%) were less than perfect. Meanwhile, for non-routine questions, only 1 person or 3.8% were able to answer correctly and 96.2% were unable to complete the questions given. This shows that the ability of students to solve random variable problems and the distribution of opportunities in the Covid-19 era in general for routine questions is still low and non-routine is very low, which indicates that students' lack of understanding and mastery of the concepts that have been conveyed through online learning